(3LhGH Ydi SDGd ef Cgd ShS aj JdGhI GdbQBfs - (3CHh HcQ Hf jhSa GdScJfjs
(3ChdgG (B:s
(3SDGd ef Ggd ShS JVef HMKkG Ydi Mce fGRdI s
(3BNQgG (B:s
(3ai GYJVO Pdc HQhGjI ai SjGb s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3eUOQ GbJfGA GdCUd (B:s
(3GdQHGW (B(609 (3c(B) s
Keywords: (3CUhd Gdabgs